Predicting who will benefit from an Expert Patients Programme self-management course - Reeves, David (Royal College of General Practitioners, 2008)
BACKGROUND: In England, the Expert Patients Programme, a lay-led chronic disease self-management course, was developed to improve self-care support and skills. The course is designed for anyone with a self-defined long-term condition, and attracts a heterogeneous group of patients. A randomised controlled trial has demonstrated effectiveness in improving subjective health. However, it is not known whether particular patient characteristics predict the impact of the course. AIM: To determine whether baseline characteristics predict clinical outcomes from attendance at a chronic disease self-management course; and to assess whether identification of such characteristics assists in targeting the course to individuals most likely to benefit. DESIGN OF STUDY: A post-hoc subgroup analysis of data from a randomised controlled trial to explore predictors of three trial outcomes: self-efficacy, energy, and health-related quality of life. SETTING: Participants with self-defined long-term conditions (n = 629) were recruited from community settings in all 28 strategic health authorities in England. METHOD: Multiple regression was used to examine interactions between baseline variables and trial outcomes. RESULTS: The predictors demonstrating significant interactions were: age and general health, and baseline values for self-efficacy, energy levels, and health-related quality of life. CONCLUSION: Participants with lower self-efficacy and health-related quality of life at baseline demonstrated more positive health outcomes. The Expert Patients Programme may have a protective effect on health-related quality of life for patients with poor health and low confidence. Younger people benefited substantially more than older people. Results suggest that positive outcomes associated with the course will be demonstrated with a wide variety of patients, although it may be worthwhile encouraging attendance of younger patients, those lacking confidence, and those coping poorly with their condition.